2015
DOI: 10.1002/jmr.2380
|View full text |Cite
|
Sign up to set email alerts
|

Insights into a type III cohesin–dockerin recognition interface from the cellulose‐degrading bacterium Ruminococcus flavefaciens

Abstract: Cellulosomes are large multicomponent cellulose-degrading assemblies found on the surfaces of cellulolytic microorganisms. Often containing hundreds of components, the self-assembly of cellulosomes is mediated by the ultra-high-affinity cohesin-dockerin interaction, which allows them to adopt the complex architectures necessary for degrading recalcitrant cellulose. Better understanding of how the cellulosome assembles and functions and what kinds of structures it adopts will further effort to develop industria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…We note that R. flavefaciens also exhibits an unusual dockerin module which binds scaffoldin A on the primary scaffoldin B. Experiments and simulations have probed the details of the cohesion-dockerin interface in various species including very recently in the cellulose-degrading bacterium R. flavefaciens; a particular valine-alanine motif was identified as important but not the sole director of interface formation, with mutation studies showing that the interface can in some cases compensate and form alternative, near iso-energetic interfaces [16] Similar results were found for the type-II cohesindockerin complex of C. thermocellum, and highlighted again the large effect the X-module can have on the cohesin-dockerin interaction [194] Multimodular enzymes, enzymes which embed various functional domains connected by linkers, are responsible for a majority of cellulose hydrolysis in nature, [4] in particular cellobiohydrolases TrCel6A and TrCel7A from T. reesei. Linkers in such enzymes are highly glycosylated, [195] e.g., in Cel6A and Cel7A, linkers (41 and 27 residues, respectively) connect the CBM to the rest of the protein which are mainly O-glycosylated with also some N-linked glycans (Cel6).…”
Section: Reviewmentioning
confidence: 97%
See 1 more Smart Citation
“…We note that R. flavefaciens also exhibits an unusual dockerin module which binds scaffoldin A on the primary scaffoldin B. Experiments and simulations have probed the details of the cohesion-dockerin interface in various species including very recently in the cellulose-degrading bacterium R. flavefaciens; a particular valine-alanine motif was identified as important but not the sole director of interface formation, with mutation studies showing that the interface can in some cases compensate and form alternative, near iso-energetic interfaces [16] Similar results were found for the type-II cohesindockerin complex of C. thermocellum, and highlighted again the large effect the X-module can have on the cohesin-dockerin interaction [194] Multimodular enzymes, enzymes which embed various functional domains connected by linkers, are responsible for a majority of cellulose hydrolysis in nature, [4] in particular cellobiohydrolases TrCel6A and TrCel7A from T. reesei. Linkers in such enzymes are highly glycosylated, [195] e.g., in Cel6A and Cel7A, linkers (41 and 27 residues, respectively) connect the CBM to the rest of the protein which are mainly O-glycosylated with also some N-linked glycans (Cel6).…”
Section: Reviewmentioning
confidence: 97%
“…Substantial advances have been made in recent years [16,59,60,75,95,98,99,[127][128][129][130] and models that are generallyaccepted (at least in gross features) exist for cellulosome structure and function, but the fine details of the molecular mechanisms are still poorly understood. For example, even appended to a CBM, it is not clear how an endoglucanase would be capable of pulling a single polysaccharide chain out of its crystalline environment and forcing the chain productively into its active site cleft.…”
Section: The Role Of Mechanostability In Nanoscale Functionmentioning
confidence: 99%
“…Previous studies identified specificity-determining residues in the dockerin module based on sequence conservation within and across different species (8,22). In a gene-swapping experiment, Nakar et al (23) were able to switch the binding specificity of a cohesin from C. cellulolyticum to dockerin of C. thermocellum by the replacement of only three residues.…”
mentioning
confidence: 99%